Hydrostatic pressure acts to stabilise a chondrogenic phenotype in porcine joint tissue derived stem cells. - Buckley, Conor; Kelly, Daniel; Ahearne, Mark; Rolfe, Rebecca (My University, 2012)
Hydrostatic pressure (HP) is a key component of the in vivo joint environment and has been shown to enhance chondrogenesis of stem cells. The objective of this study was to investigate the interaction between HP and TGF-?3 on both the initiation and maintenance of a chondrogenic phenotype for joint tissue derived stem cells. Pellets generated from porcine chondrocytes (CCs), synovial membrane derived stem cells (SDSCs) and infrapatellar fat pad derived stem cells (FPSCs) were subjected to 10 MPa of cyclic HP (4 h/day) and different concentrations of TGF-?3 (0, 1 and 10 ng/mL) for 14 days. CCs and stem cells were observed to respond differentially to both HP and TGF-?3 stimulation. HP in the absence of TGF-?3 did not induce robust chondrogenic differentiation of stem cells. At low concentrations of TGF-?3 (1 ng/mL), HP acted to enhance chondrogenesis of both SDSCs and FPSCs, as evident by a 3-fold increase in Sox9 expression and a signifi cant increase in glycosaminoglycan accumulation. In contrast, HP had no effect on cartilage-specifi c matrix synthesis at higher concentrations of TGF-?3 (10 ng/mL).
PUBLISHED
discussion 133-4
Keywords: Hydrostatic pressure; Hydrostatic pressure; Next Generation Medical Devices; Developmental Biology